Case report: Investigation of genetic mutations in a case of schistosomus reflexus in a Holstein dairy cattle fetus in Korea - Park, Woncheoul; Chai, Han-Ha; Lim, Dajeong; Dang, Changgwon; Lee, Jaegu; Kim, Jongho; Jeong, Hogyun; Lee, Taekwon; Lee, Ki-Chang; Lee, Kyunghyun (Frontiers in Veterinary Science, 2023)
Schistosomus reflexus (SR) is one of the most common congenital anomalies found in cases of cattle dystocia, and it occurs mostly in cattle. Congenital anomalies such as SR are caused by various genetic and environmental factors, but no specific cause has been elucidated. This study reports a case of schistosomus reflexus (SR) in a fetus with congenital anomalies in Holstein dairy cattle in Korea.Grossly, a distinct spine curvature was observed between the thoracic and lumbar vertebrae and a consequential malformation from the sacrum to the occipital. Furthermore, the thoracic and abdominal organs were exposed to the outside. In the Computed Tomography (CT) images, mild and severe kyphoscoliosis was observed in T1~11 and L1~6, respectively. Additionally, vertebrae dysplasia was observed in S1~5 and Cd 1~5. To pinpoint the causal genes and mutations, we leveraged the custom 50K Hanwoo SNP-Chip and Online Mendelian Inheritance in Animals (OMIA) database. As a result, we identified a nonsense mutation in apoptotic protease activating factor 1 (APAF1) within HH1 that was associated with a decrease in conception rate and an increase in abortion in Holstein dairy cattle. The genotype of the SR case was A/A, and most of the 1142 normal Holstein dairy cattle as a control group were G/G. In addition, the A/A genotype did not exist in the control group. Based on the pathological, genetic, and radiological findings, congenital abnormalities were diagnosed as schistosomus reflexus.